Image encounters : Moche murals and archaeo art history - Trever, Lisa (Austin : University of Texas Press, 2022)
Moche murals of northern Peru represent one of the great, yet still largely unknown, artistic traditions of the ancient Americas. Created in an era without written scripts, these murals are key to understandings of Moche history, society, and culture. In this first comprehensive study on the subject, Lisa Trever develops an interdisciplinary methodology of "archaeo art history" to examine how ancient histories of art can be written without texts, boldly inverting the typical relationship of art to archaeology. Trever argues that early coastal artistic traditions cannot be reduced uncritically to interpretations based in much later Inca histories of the Andean highlands. Instead, the author seeks the origins of Moche mural art, and its emphasis on figuration, in the deep past of the Pacific coast of South America. Image Encounters shows how formal transformations in Moche mural art, before and after the seventh century, were part of broader changes to the work that images were made to perform at Huacas de Moche, El Brujo, Pañamarca, and elsewhere in an increasingly complex social and political world. In doing so, this book reveals alternative evidentiary foundations for histories of art and visual experience.
Introduction : image encounters -- Chapter 1. Mural origins and coastal corporealities -- Chapter 2. Formulating traditions : ancestral divinities, Norcosteno design, and the aesthetics of replication in Moche mural art (200-650 CE) -- Chapter 3. Siting narratives : Moche mural painting and the condensation of a medium (650-850 CE) -- Chapter 4. Archaeo-iconology : an archaeology of image experience and response -- Conclusion : on the Huaca.
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (viewed Janurary 17, 2022).
In English.
JSTOR
Keywords: Mochica mural painting and decoration -- Peru -- Pañamarca Site; Mochica Indians -- Peru -- Pañamarca Site -- Antiquities; Mural painting and decoration, Peruvian; Indian mural painting and decoration; Huacas -- Peru; Huacas -- Pérou.; ART / General; Huacas; Indian mural painting and decoration; Mochica Indians -- Antiquities; Mochica mural painting and decoration; Mural painting and decoration, Peruvian; Peru; Peru -- Pañamarca Site; Moche art, Moche, mural art, Peruvian art, art history, archaeology, Pre-Columbian, pre-columbian art, pre-columbian archaeology; Electronic books